HADIS SHAHIH DAN HADIS DHAIF: ANALISIS BENTUK-BENTUK DAN KEHUJJAHANNYA: ṢAḤĪḤ HADITH AND ḌAʿĪF HADITH: AN ANALYSIS OF THEIR FORMS AND AUTHORITATIVENESS - Muhammad Husein Isfa Hani; Muh. Habibulloh (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study examines the quality of hadiths through an analysis of the criteria for authenticity and weakness based on the science of musthalah al-hadith, while also assessing their authority within Islamic jurisprudence, legal theory, and contemporary practice. The findings indicate that authentic (sahih) hadiths possess strong validity as legal sources due to their reliable chains of transmission and consistent textual integrity, whereas weak (dhaif) hadiths require caution and are accepted only within limited contexts such as virtuous deeds. The study highlights methodological differences among classical and contemporary scholars regarding the use of weak hadiths. Furthermore, modern digital platforms significantly influence the circulation of hadiths, emphasizing the urgency of strengthening religious literacy so society can distinguish textual authenticity. This research underscores the importance of hadith criticism methodology in preserving the integrity of Islamic teachings and ensuring accurate public understanding.